Method for producing powder material for thermal spraying and coating film

The use of a solution powder material with a defined resin-to-ceramic particle ratio forms a coating film with uniform pores, addressing the wear resistance and heat conductivity issues of conventional films.

JP7623876B2Active Publication Date: 2025-01-29FUJIMI INCORPORATED
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021059742
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-01-29
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Conventional coating films formed using mixed powder materials suffer from reduced wear resistance due to the formation of pores, compromising their balance of low heat conductivity and high wear resistance.

Method used

A solution powder material composed of secondary particles with a specific ratio of resin and ceramic primary particles, where the median diameter of the secondary particles to the primary resin particles is 2 or more, forming a uniform porous structure in the coating film.

Benefits of technology

The solution powder material achieves a coating film with balanced low heat conductivity and high wear resistance by ensuring uniform pore distribution and appropriate particle sizing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623876000002
    Figure 0007623876000002
  • Figure 0007623876000003
    Figure 0007623876000003
  • Figure 0007623876000004
    Figure 0007623876000004
Patent Text Reader

Abstract

To provide a powder material for thermal spraying that forms a thermal-sprayed coating having both of low thermal conductivity and high abrasion resistance, and a method for producing a coating using the same.SOLUTION: A powder material for thermal spraying comprises composite secondary particles comprising primary particles of resin particles and primary particles of ceramic particles. The ratio of the median diameter of the composite secondary particles to the median diameter of the primary particles of the resin particles is 2 or more.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermal spray powder, a method for producing the same, and a method for producing a coating film using the same. More specifically, the present invention relates to a thermal spray powder capable of forming a coating film having both extremely high abrasion resistance and low thermal conductivity compared to conventional products, for a heat-resistant material used in a high-temperature environment, and a coating film using the same. [Background technology]

[0002] In materials used under high temperatures, such as the stationary blades, moving blades, and wall materials of combustors of gas turbine engines, heat-resistant members are covered with a heat-shielding film to protect them from high temperatures. The coating film has a structure in which, for example, an undercoat layer and a topcoat layer are laminated on top of it. These coating films are formed, for example, by a thermal spraying method. The thermal spraying method is one of the surface modification techniques that has been put to practical use, along with physical vapor deposition and chemical vapor deposition. The thermal spraying method has features such as no limitations on the size of the substrate, the ability to form a uniform thermal sprayed film even on a substrate with a large area, a high film formation speed, ease of on-site application, and the ability to form a thick film relatively easily, and therefore has been widely applied to various industries in recent years and has become an extremely important surface modification technique. Patent Document 1 proposes a method in which a thermal spray material consisting of a mixed powder of ceramic powder and resin powder is thermally sprayed onto an undercoat layer to form a topcoat layer, and then a heat treatment is performed to vaporize the resin powder in the topcoat layer and form pores in the topcoat layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-181192 A Summary of the Invention [Problem to be solved by the invention]

[0004] A coating film formed using a thermal spray powder material consisting of a conventional mixed powder has a reduced thermal conductivity due to the formation of pores, but the abrasion resistance of the coating also decreases. Therefore, an object of the present invention is to provide a thermal spray powder material for forming a coating film that has both low thermal conductivity and high abrasion resistance, and a method for producing a coating film using the same. [Means for solving the problem]

[0005] In order to solve the above problems, the present invention provides a powder material for thermal spraying, which contains composite secondary particles composed of primary particles of resin particles and ceramic particles, and the ratio of the median diameter of the composite secondary particles to the median diameter of the primary particles of the resin particles is 2 or more. Effect of the Invention

[0006] By setting the ratio of the median diameter of the composite secondary particles to the median diameter of the primary particles of the resin particles to be 2 or more, a uniform porous structure can be formed in the coating film, which makes it possible to form a coating film that has both low thermal conductivity and high abrasion resistance. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1(a) shows a scanning electron microscope (SEM) photograph of the surface structure of a resin particle used in conventional composite secondary particles, (b) shows a scanning electron microscope (SEM) photograph of the surface structure of a resin particle used in a composite secondary particle of an embodiment of the present invention, (c) shows a scanning electron microscope (SEM) photograph of the surface structure of a ceramic particle used in conventional composite secondary particles, and (d) shows a scanning electron microscope (SEM) photograph of the surface structure of a ceramic particle used in a composite secondary particle of an embodiment of the present invention. [Diagram 2]FIG. 2(a) shows a scanning electron microscope (SEM) photograph of the surface structure of a composite secondary particle of ceramic particles and resin particles according to an embodiment of the present invention, (b) shows a scanning electron microscope (SEM) photograph of the cross-sectional structure of a composite secondary particle of ceramic particles and resin particles according to an embodiment of the present invention, and (c) is an enlarged view of (a). [Diagram 3] Figure 3(a) shows a scanning electron microscope (SEM) photograph of the surface structure of a composite secondary particle of a comparative example of the present invention, and (b) shows a scanning electron microscope (SEM) photograph of the cross-sectional structure of a composite secondary particle of a comparative example of the present invention. [Figure 4] FIG. 4 shows a scanning electron microscope (SEM) photograph of the cross-sectional structure of a coating sprayed with composite secondary particles of a comparative example of the present invention. [Diagram 5] 1 shows a scanning electron microscope (SEM) photograph of the cross-sectional structure of a coating sprayed with composite secondary particles according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] An embodiment of the present invention will be described in detail. Note that the following embodiment shows an example of the present invention, and the present invention is not limited to this embodiment. In addition, various modifications and improvements can be made to the following embodiment, and such modifications and improvements can also be included in the present invention. One embodiment of the present invention provides a powder material for thermal spraying, which contains composite secondary particles composed of primary particles of resin particles and ceramic particles, and in which the ratio of the median diameter of the composite secondary particles to the median diameter of the primary particles of the resin particles is at least 2. More specifically, the powder material for thermal spraying of this embodiment may contain composite secondary particles obtained by granulating resin raw material particles and ceramic raw material particles.

[0009] The median diameter is the cumulative 50% particle diameter (Dv50%) from the fine particle side of the cumulative particle size distribution based on volume, and can be measured, for example, by a laser diffraction particle size distribution measuring device. Specifically, the laser diffraction particle size distribution measuring device Mastersizer 3000 manufactured by Malvern Panalytical can be used as the laser diffraction particle size distribution measuring device. In this embodiment, the primary particle diameter of the resin particles is the median diameter of the resin raw material particles. Moreover, the primary particle diameter of the ceramic particles is the median diameter of the ceramic raw material particles.

[0010] By forming a coating film using the thermal spray powder of one embodiment, a uniform porous structure can be formed in the coating film, which allows the formation of a coating film that has both low thermal conductivity and high abrasion resistance. The ratio of the median diameter of the composite secondary particles to the median diameter of the primary particles of the resin particles may be 3 or more, 4 or more, or 5 or more. If the ratio of the median diameter of the composite secondary particles to the median diameter of the primary particles of the resin particles is less than 2, the pores in the coating after thermal spraying tend to become coarse. Also, if this ratio is less than 2, the pore distribution tends to become non-uniform.

[0011] The ratio of the median diameter of the primary ceramic particles to the median diameter of the composite secondary particles is not particularly limited, but may be at least 20, at least 25, or at least 30. The larger the ratio of the median diameter of the composite secondary particles to the median diameter of the primary ceramic particles, the more improved the wear resistance tends to be.

[0012] In the composite secondary particles, it is preferable that each resin particle is surrounded by a plurality of ceramic particles. In addition, it is preferable that the outermost shell of the composite secondary particles is formed by ceramic particles. In other words, it is preferable that the resin particles are not exposed on the surface of the composite secondary particles. This is advantageous for suppressing the volatilization of the resin particles during the thermal spraying process and forming pores in the coating film. In addition, it is preferable that the composite secondary particles are spherical from the viewpoint of fluidity. In this embodiment, the spherical shape refers to, for example, a particle having an average circularity of 0.8 or more and 1.0 or less. In addition, the non-spherical shape refers to a particle having an average circularity of less than 0.8. The average circularity means the arithmetic average value of the circularity in a plan view of, for example, 1000 or more composite secondary particles obtained by an image analysis method.

[0013] In one embodiment of the present invention, the ratio of the median diameter of the primary particles of the ceramic particles to the median diameter of the primary particles of the resin particles is not particularly limited. When the median diameter of the primary particles of the resin particles is larger than the median diameter of the primary particles of the ceramic particles, the ceramic particles tend to adhere to the resin particles so as to cover them. The ratio of the median diameter of the primary particles of the resin particles to the median diameter of the primary particles of the ceramic particles is preferably greater than 1, and more preferably 3 or more. The ratio of the median diameter of the primary particles of the resin particles to the median diameter of the primary particles of the ceramic particles may be less than 7, or 5 or less, from the viewpoint of suppressing the deterioration of the wear resistance.

[0014] In one embodiment of the present invention, the median diameter of the composite secondary particles composed of primary particles of ceramic particles and resin particles is not particularly limited. However, if the median diameter is too large, it tends to be difficult to form a uniform and dense coating film, so the median diameter of the composite secondary particles is preferably 40 μm or less. The median diameter of the composite secondary particles may be 35 μm or less, or 30 μm or less. The median diameter of the composite secondary particles is preferably 5 μm or more, and more preferably 10 μm or more. If the median diameter of the composite secondary particles is less than 5 μm, it is difficult to form a coating structure in which the resin particles are covered with the ceramic particles, and if it is less than 10 μm, it is difficult to supply the composite secondary particles to a thermal spray machine.

[0015] <Ceramic particles> The type of ceramic forming the ceramic particles is not particularly limited, and metal oxides such as yttrium oxide (Y2O3), aluminum oxide (Al2O3), silicon oxide (SiO2), titanium oxide (TiO2), and zirconium oxide (ZrO2) can be suitably used, but zirconium oxide (zirconia) is preferred. Among zirconia, yttria (Y2O3) stabilized zirconia (YSZ), ytterbia (Yb2O3) stabilized zirconia (YbSZ), dysprosia (Dy2O3) stabilized zirconia (DySZ), erbia (Er2O3) stabilized zirconia (ErSZ), and SmYbZr2O7 are particularly preferred. Among yttria stabilized zirconia, zirconia stabilized with 8 mass% yttria (8YSZ) is more preferred.

[0016] The median diameter of the primary particles of the ceramic particles is not particularly limited, but may be 1 μm or less. If it exceeds 1 μm, it tends to be difficult to form composite secondary particles in which the surfaces of resin particles are coated with ceramic particles. For example, as shown in FIG. 1(d), ceramic particles having a smaller median diameter and a uniform particle diameter can be used compared to the ceramic particles used in the conventional (comparative) composite secondary particles shown in FIG. 1(c). In addition, the ceramic particles of this embodiment are non-spherical, specifically, have irregular polygonal surfaces.

[0017] <Resin particles> The type of resin forming the resin particles is not particularly limited as long as it is a resin that is thermally decomposed and vaporized by heating, but a resin whose thermal decomposition temperature in air is 200°C or higher is preferable. The thermal decomposition temperature in air can be measured, for example, by thermogravimetry-differential thermal analysis (TG-DTA). If the 5% weight loss temperature in air by TG-DTA is 200°C or higher, it can be determined that the thermal decomposition temperature in air is 200°C or higher.

[0018] Examples of resins having a thermal decomposition temperature of 200°C or higher in air include aliphatic polyamides, aromatic polyamides, polyimides, polyetherimides, polyamideimides, polysulfones, polyethersulfones, polyphenylene sulfide, polyetheretherketones, polyarylates, polycarbonates, fluororesins, liquid crystal polymers, phenolic resins, urea resins, silicon resins, epoxy resins, polyesters, aromatic polyesters, polyacetals, polybutylene terephthalates, polymethyl methacrylates, and melamine resins. As the resin particles, resins with high heat resistance are preferred. Among these, polyimides, polyesters, aromatic polyesters, polymethyl methacrylates, polycarbonates, phenolic resins, and melamine resins are preferred. In addition, the combination of the types of ceramic particles and resin particles is not particularly limited, but when 8YSZ is used for the ceramic particles, it is preferred to use polyimides and polyesters, aromatic polyesters, polymethyl methacrylates, and combinations thereof for the resin particles.

[0019] The content of resin particles in the thermal spray powder can be determined from the amount of resin raw material particles mixed during the production of the composite secondary particles. The content of resin particles is preferably 10% by volume or more and 50% by volume or less, more preferably 15% by volume or more and 40% by volume or less, relative to the entire thermal spray powder, i.e., the total amount of ceramic particles mixed and resin particles mixed. The content of resin particles can be practically measured by converting the amount of carbon measured using a carbon analyzer into the amount of resin particles mixed. Specifically, the carbon analyzer EMIA-321V2 made by HORIBA can be used as the carbon analyzer. As a measurement method, the amount of carbon per unit weight of the raw resin (resin particles) is measured in advance, or a known amount of carbon is obtained. Next, the carbon amount of the composite secondary particles adjusted by the resin particles and the ceramic particles is measured. Since the amount of carbon in the composite secondary particles is substantially due to the resin particles, the carbon amount of the composite secondary particles can be converted into the amount of resin particles mixed. One example of the converted content is the polyimide converted content, which is obtained by converting the amount of carbon using the weight ratio of carbon element in polyimide. The polyimide-equivalent content of resin particles in the thermal spray powder is preferably 1% by weight or more and 12% by weight or less, and more preferably 5% by weight or more and 10% by weight or less. In general, as the resin particle content increases, the porosity of the coating film after thermal spraying tends to increase and the thermal conductivity tends to decrease, but the abrasion resistance tends to decrease. When the amount of resin particles mixed is 10% by volume or more, or the polyimide-equivalent content is 1% by weight or more, the porosity tends to increase and the thermal conductivity tends to be sufficiently low. Also, when the amount of resin particles mixed is 50% by volume or less, or the polyimide-equivalent content is 12% by weight or less, sufficient abrasion resistance tends to be obtained.

[0020] The median diameter of the primary particles of the resin particles is not limited, but is preferably 10 μm or less, and more preferably 5 μm or less. For example, as shown in FIG. 1(b), resin particles having a smaller median diameter and a uniform particle diameter can be used compared to the resin particles used in the conventional (comparative) composite secondary particles shown in FIG. 1(a). The resin particles of this embodiment may be non-spherical but spherical.

[0021] <Method of manufacturing powder for thermal spraying> The thermal spray powder of the present invention can be produced by a method including a step of mixing and granulating each raw material particle. Although there is no particular limitation, in general, a spherical powder with a uniform particle size that can be obtained by classifying a spherical granular powder obtained by mixing and granulating each raw material particle is preferred. Specifically, it can be produced by a granulation method or the like. The granulation method can be carried out by utilizing a granulation method such as dry granulation or wet granulation. Specific examples of the granulation method include rolling granulation, fluidized bed granulation, stirring granulation, crushing granulation, melt granulation, spray granulation, and microemulsion granulation. Among them, spray granulation is a preferred granulation method.

[0022] <Method of forming coating film> The method for forming a coating film using the thermal spray material of the present invention includes a step of forming a thermal spray coating by thermally spraying the thermal spray powder material formed by the above-mentioned method onto a substrate, and a heating step of subjecting the thermal spray coating to a heat treatment. Through these steps, a coating film made of ceramics that forms ceramic particles is formed, and pores are formed in the coating film.

[0023] By using the powder material for thermal spraying and performing thermal spraying by various thermal spraying methods, it is possible to form a thermal spray coating on various substrates. The thermal spraying method is not particularly limited, but for example, plasma spraying methods such as atmospheric plasma spraying (APS), suspension plasma spraying (SPS), low pressure plasma spraying (LPS), and high pressure plasma spraying, high velocity flame spraying such as high velocity oxygen flame (HVOP) spraying, warm spray spraying, and high velocity air flame (HVAF) spraying, etc. can be suitably used.

[0024] The substrate on which the thermal spray coating is formed is subjected to a heat treatment, and the thermal spray coating is heated to a high temperature, whereby the resin particles dispersed in the matrix of the thermal spray coating can be thermally decomposed and vaporized. The heat treatment may be performed in an air atmosphere. In the heat treatment, the substrate is heated to a temperature equal to or higher than the temperature at which the resin forming the resin particles is thermally decomposed and vaporized. Specifically, the substrate is preferably heated to a temperature equal to or higher than the thermal decomposition temperature of the resin forming the resin particles in air, for example, a temperature equal to or higher than the 5% weight loss temperature in air by TG-DTA. The gas generated by the thermal decomposition of the resin particles is discharged outside the thermal spray coating, and the portions where the resin particles were present become voids, so that pores are formed in the matrix of the thermal spray coating. As a result, a coating coating in which pores are dispersed in the matrix made of ceramic is obtained. If the median diameter of the primary particles of the resin particles is smaller than the median diameter of the composite secondary particles, a coating coating in which relatively fine pores are dispersed in the coating is obtained.

[0025] The coating film may have a structure in which an undercoat layer and a topcoat layer are laminated on the undercoat layer. The thermal spray powder produced by the above method may be used to form the undercoat layer or the topcoat layer. The thermal spray powder material produced by the above method can be supplied to the thermal spray device in the form of a powder, or in the form of a slurry. When the thermal spray material is in the form of a slurry, it can be prepared using a dispersion medium. Examples of the dispersion medium include alcohols such as methanol and ethanol, toluene, hexane, and kerosene. The slurry thermal spray material may further contain other additives such as a dispersant, a flocculant, and a viscosity modifier.

[0026] The type of substrate on which the coating film is formed is not particularly limited. Examples of the substrate include metal materials such as alloys, simple ceramic materials, composite ceramic materials, ceramic matrix composites, etc. Specific examples of metal materials include alloys containing iron, nickel, cobalt, etc. Examples of the substrate include stainless steel, Hastelloy (manufactured by Haynes Corporation), which is an alloy in which molybdenum, chromium, etc. are added to a nickel base, Inconel (manufactured by Special Metals Corporation), which is an alloy in which iron, chromium, niobium, molybdenum, etc. are added to a nickel base, Stellite (manufactured by Deloro Stellite Group), which is an alloy mainly composed of cobalt and to which chromium, tungsten, etc. are added, and Invar, which is an alloy in which nickel, manganese, carbon, etc. are added to iron, etc. Examples of the ceramic materials include monolithic ceramics such as zirconia and alumina, and ceramic matrix composites (CMCs).

[0027] Desirable properties of the coating film include high abrasion resistance and low thermal conductivity. For abrasion resistance, the amount of abrasion measured by the Suga abrasion test is reduced compared to conventional coating films. Specifically, the amount of abrasion measured by the Suga abrasion test is preferably 0.33 μm / lap or less. Thermal conductivity should be reduced to the same level as conventional coating films. Specifically, it is preferably 0.49 W / m·K or less. Also, assuming that the porosity and thermal conductivity of the coating film are proportional, the porosity can be used to evaluate thermal conductivity. Specifically, the porosity is preferably 10% or more. EXAMPLES

[0028] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples in any way. <Preparation of powder material for thermal spraying> As ceramic particles, ZrO2-8 mass% Y2O3 (YSZ) with a median diameter (Dv50%) shown in Table 1 was used, as resin particles, resin particles with the type and median diameter shown in Table 1 were used, and 2 mass% polyvinyl alcohol (PVA) was added as a binder. These were blended in the ratio shown in Table 1, mixed, and granulated to prepare secondary particles of Examples 1 to 6 and Comparative Examples 2 and 3. First, the ceramic particles and resin particles were mixed in a predetermined blend, and the mixture was dispersed in a solvent consisting of a mixed solution of water and alcohol together with 2 mass% PVA with respect to 100 mass% of this mixed powder to prepare a slurry. In Comparative Example 1, a slurry was prepared in the same manner using only YSZ ceramic particles. Next, these slurries were granulated into droplets using a spray granulator and then dried to prepare thermal spray powder materials (secondary particles) of Examples 1 to 6 and Comparative Examples 2 and 3 consisting of composite secondary particles of resin particles and ceramic particles, and thermal spray powder material (secondary particles) of Comparative Example 1 consisting of secondary particles of ceramic particles. Table 1 shows the particle size ratio of the median diameter of the primary particles of the resin particles to the median diameter of the obtained composite secondary particles.

[0029] [Table 1]

[0030] The median diameter of each particle was measured using a laser diffraction particle size distribution analyzer, Mastersizer 3000, manufactured by Malvern Panalytical, as the cumulative 50% particle diameter (Dv50%) from the fine particle side of the cumulative particle size distribution based on volume. The obtained thermal spray powder was observed using a scanning electron microscope (SEM). As shown in Figures 2(a) and (c), the thermal spray powder of Example 2 contained composite secondary particles composed of primary particles of resin particles and ceramic particles. The composite secondary particles were spherical. The spherical shape means that the average circularity of the particles is, for example, 0.8 to 1.0.

[0031] As shown in Fig. 2(b), in the composite secondary particles, the resin particles were surrounded by ceramic particles. The outermost shell of the composite secondary particles was formed by ceramic particles. The morphology of the composite secondary particles in Examples 1 and 3 to 6 was also similar to that in Example 2. As shown in FIGS. 3(a) and (b), in Comparative Example 3, compared with the Examples, composite secondary particles were contained in which the resin particles were coarse relative to the median diameter of the composite secondary particles.

[0032] <Formation of coating film> The thermal spray powder materials of Examples 1 to 6 and Comparative Examples 1 to 3 produced by the above method were used to form a thermal spray coating under the following conditions (1), and then the thermal spray coating was heat-treated under the conditions (2) to form a coating film. (1) Thermal spray conditions The thermal spraying machine used was the SG-100 plasma made by PRAXAIR Co., Ltd. The thermal spraying conditions are as follows: Ar partial pressure: 50 psi He partial pressure: 50 psi Powder flow rate: 15g / min Substrate: Stainless steel SUS316 blasted with alumina #40 Spray distance: 150mm Coating thickness: 200-300μm (for thermal conductivity measurement samples, made at 700-1000μm) (2) Heat treatment The substrate on which the thermal spray coating was formed in the above thermal spray test was subjected to a heat treatment in an air atmosphere to vaporize the resin in the thermal spray coating and form pores. The heat treatment was performed in an air furnace at a heating temperature of 700°C for 2 hours.

[0033] When composite secondary particles containing coarse resin particles relative to the median diameter of the composite secondary particles were used for thermal spraying as in Comparative Example 3 shown in Figure 4, coarse pores of about 50 μm were formed in the coating film. This is thought to contribute to a decrease in abrasion resistance. Fig. 5 shows a scanning electron microscope (SEM) photograph of a cross section of a coating film formed from the thermal spray powder of Example 2 as a representative example of an embodiment of the present invention. It can be seen from this that fine pores of about 2 to 5 µm are uniformly formed in the film. Such a uniform pore distribution is not seen in a thermal spray film formed from a thermal spray powder made of a conventional mixed powder, nor is it seen in the comparative example containing coarse resin particles. It can therefore be seen that the inclusion of fine resin particles allows fine pores to be uniformly formed in the film.

[0034] <Measurement of coating film properties> For the coating films of Examples 1 to 6 and Comparative Examples 1 to 3 produced by the above method, the porosity, wear characteristics, and thermal conductivity were measured by the following methods. (1) Porosity The coating film obtained by heat treating the thermal spray coating formed under the above conditions was cut, the cross section was polished to a mirror finish, and the cross section was observed under a microscope to measure the percentage of pores in a unit cross-sectional area. (2) Thermal conductivity The thermal conductivity λ of the coating film can be calculated using the following formula: λ=Cp×a×ρ In the above formula, Cp is the specific heat capacity (J kg -1 ·K -1 ), a is the thermal diffusion coefficient (m 2 ·S -1 ), ρ(kg m -3 ) is the density. The specific heat capacity Cp (J kg -1 ·K -1 ) and thermal diffusion coefficient (m 2 ·S -1 ) was measured using a Netch LFA467HT Hyper Flash. (3) Evaluation of wear characteristics The coating film formed in the above thermal spray test was subjected to a load of 1 kgf using a Suga abrasion resistance tester, and the reduction in thickness of the coating film due to abrasion with #180 abrasive paper was measured.

[0035] As can be seen from Table 1, the coating films of Examples 1 to 6 have excellent abrasion resistance despite their high porosity, but in Comparative Examples 2 and 3, in which the median diameter of the composite secondary particles relative to the median diameter of the primary particles of the resin particles is less than 2, the abrasion resistance is reduced (the abrasion rate is increased). It was confirmed that the coating films of Examples 2 and 3 have low thermal conductivity. Although the thermal conductivity was not measured for Examples 1 and 4 to 6, it is presumed that the thermal conductivity is low because the porosity is sufficiently high. It was also confirmed that Comparative Example 1, which does not use resin particles, had low porosity and did not sufficiently reduce thermal conductivity. [Industrial Applicability]

[0036] According to the thermal spray powder of the present invention, a uniform porous structure can be formed in the coating film, thereby providing a coating film that has high industrial applicability and combines low thermal conductivity with high abrasion resistance.

Claims

1. Composite secondary particles composed of primary particles of resin particles and primary particles of ceramic particles, a ratio of a median diameter of the composite secondary particles to a median diameter of the primary particles of the resin particles is 2 or more; The median diameter of the primary particles of the resin particles is 4 μm or more and 12 μm or less, The median diameter of the primary particle diameter of the ceramic particles is 1 μm or less, The median diameter of the composite secondary particles is 10 μm or more and 40 μm or less, The content of the resin particles is 10% by volume or more and 50% by volume or less, The thermal spray powder material has a coating structure in which the resin particles are covered with the ceramic particles.

2. 2. The thermal spray powder according to claim 1, wherein a ratio of a median diameter of the composite secondary particles to a median diameter of the primary particles of the ceramic particles is 20 or more.

3. 3. The thermal spray powder according to claim 1, wherein a ratio of a median diameter of primary particles of the resin particles to a median diameter of primary particles of the ceramic particles is less than 7.

4. 4. The thermal spray powder according to claim 1, wherein the resin particles have a median primary particle diameter of 10 μm or less.

5. A method for producing a powder material for thermal spraying, comprising the steps of: Mixing and granulating the resin particles and the ceramic particles; a ratio of a median diameter of the composite secondary particles after granulation to a median diameter of the primary particles of the resin particles is 2 or more; The median diameter of the primary particles of the resin particles is 4 μm or more and 12 μm or less, The median diameter of the primary particle diameter of the ceramic particles is 1 μm or less, The median diameter of the composite secondary particles is 10 μm or more and 40 μm or less, The content of the resin particles is 10% by volume or more and 50% by volume or less, The method for producing a powder material for thermal spraying has a coating structure in which the resin particles are covered with the ceramic particles.

6. A step of forming a thermal spray coating by thermal spraying the thermal spray powder material according to any one of claims 1 to 4 onto a substrate; a heating step of subjecting the thermal spray coating to a heat treatment; A method for producing a coating film comprising the steps of:

Citation Information

Patent Citations

  • Fire resistant material for spraying

    JP1981108871A

  • Thermal spraying powder in which specified high temperature polymer is taken

    JP2000144363A

  • Method for producing thermal barrier coating material

    JP2013181192A

  • Composite powder material for forming spray coating film and method for producing the same and composite spray coating film

    JP2014181348A

  • Ceramic shell thermal spray powders and methods of use thereof

    US20030129320A1